Kualitas Pelayanan Bus Rapid Trans Semarang (BRT) Koridor II di Kota Semarang (dengan Rute Terminal Terboyo Semarang-Terminal Sisemut Ungaran) - Arinha Pratitha Maitri; Susi Sulandari; Rihandoyo Rihandoyo (Journal of Public Policy and Management Review, 2014)
Services is a Success key of various businesses or services activities. The role of servicing gets bigger and determined when there’s service in community activities. Public service scope are very wide, one of them is the transportation service. There’s Semarang BRT as part of the transportation system in Semarang city, and its one of Semarang community needs at transportation area. BLU UPTD Mangkang Terminal Section as Semarang BRT management had a vision “ Creating a Professional, Independent, reliable, sustainable and affordable service”.The objective of research was to identify BRT Semarang corridor II service quality. To identify How does the quality of service that has been given from BRT Semarang corridor II to the community and also what kind of dimensions can be the inhibitor of BRT Semarang corridor II service quality. A measure of the quality, seen from 8 quality service dimensions that has been formulated. The research used a descriptive qualitative with repondents from BLU Semarang city employeses and BRT Semarang corridor II user.The result of the research are the BRT Semarang corridor II quality service was good enough if identified from 8 dimensions quality services, only at direct tangibles dimension and officer reliability that needs to be improved.